Cavy lifespan: survival analysis and lifetables for the pet guinea pig (Cavia porcellus, L.) in Britain - Fernando Mata (PeerJ)
In Britain, an estimated number of 700,000 guinea pigs are currently kept as pets. Despite their widespread presence, research on pet guinea pig survivability remains limited. While demographic studies exist, they primarily focus on morbidity rather than lifespan analysis. This study aims to fill this gap by investigating factors influencing pet guinea pig longevity and constructing life tables, contributing valuable insights into their survival patterns and potential improvements in care practices. The study was conducted using publicly available data from the VetCompass™ UK Program, including 675 guinea pigs receiving veterinary care in the UK in 2019. The survival analysis was conducted using Kaplan–Meier models, with lifespan differences tested via the Log-Rank test. Key predictors included sex, neutering status, and breed classification. The results of the study indicate an average lifespan of the British pet guinea pigs is 4.022 (3.875; 4,170) years; a median survival time of 4.025 95% confidence interval (3.830; 4,290) years; and an interquartile range of (2.563; 5447) years. Unlike other companion animals, no significant differences in longevity were found between sexes, neutering status, or breed (log-rank Mantel-Cox χ2 p > 0.05), suggesting that these factors may play a less critical role in guinea pigs. The findings challenge common assumptions about lifespan determinants in domesticated species. The study also highlights low neutering rates, likely influenced by concerns over surgical risks. Additionally, breed classification remains inconsistent, indicating a possible lack of standardised identification among owners and veterinarians. This study is limited by potential selection bias, lack of environmental and husbandry data, few neutered animals, unclear breeding backgrounds, unaccounted cohort effects, and no geographical analysis of care variation across different regions of Britain.